Investigating the perceived effectiveness of digital technology for elite athlete support in golf - Mears, A.; Phillips, I.; Sumner, J. (Proceedings of the 7th International Conference on Sport Sciences Research and Technology Support icSPORTS - Volume 1, 2019)
Digital technologies have enabled vast and varied amounts of data to be captured on elite athletes. The data is intended for use by athletes, coaches and support team e.g. physiotherapists, sports scientists for many purposes including performance development or injury prevention. However, the usefulness of such digital technologies and the information gathered is only beneficial if deemed effective by all those involved. The purpose of this study was to investigate the effectiveness of digital technology for elite athletes` development and support from athlete, coach and support team perspective in golf. Interviews were conducted with athletes, coaches and support team for a sport where digital technologies were used to facilitate training. The results of the study uncovered four categories that helped to understand how effectiveness was perceived which were "The Influence on Psychological Well-being and Proprioception", "Measurement Uncertainty", "Environment" and "Type, Ease and F requency of Use". Exploring these categories provided insight into the best practices for digital technology integration into elite athlete support and ultimately can help shape future developments of digital technologies.